Toxicity of endosulfan on embryo-larval development of the South American toad Rhinella arenarum - Svartz, Gabriela Veronica (2014)
Endosulfan is a widely used pesticide despite its extreme toxicity to a variety of taxa and its worldwide ban. The aim of the present study was to evaluate the acute and chronic toxicity of endosulfan on the embryonic-larval development of the common South American toad Rhinella arenarum. The results showed that lethal and sublethal effects increased with concentration and exposure time. The sensitivity to endosulfan increased during the larval period, the complete operculum stage (S.25) being the most sensitive (504-h median lethal concentration [LC50]=0.01mg endosulfan/L; 10% lethal concentration [LC10]=0.004mg endosulfan/L). Endosulfan exposure caused morphological abnormalities such as general underdevelopment, edema, gill malformations, and cellular dissociation as well as neurotoxicity. Our results also showed that larvae exposed to concentrations of 0.005mg endosulfan/L and 0.01mg endosulfan/L completed metamorphosis earlier than controls, but with underdevelopment. The 240-h teratogenic index was 6.13, implying a high risk for embryos to be malformed in the absence of significant embryonic lethality. Because the hazard quotients for chronic exposure were over 1, the level of concern value and toxicity endpoints obtained in the present study for R. arenarum occurred at concentrations lower than the levels of endosulfan reported in the environment, this pesticide should be considered a potential risk for this species. Environ Toxicol Chem 2014;33:875-881.